MAPPING THE CONCEPTUAL VOID: A BIBLIOMETRIC ANALYSIS OF DEFENSE ENTREPRENEURSHIP IN GLOBAL AND INDONESIAN DEFENSE INDUSTRY LITERATURE (2000–2025) - Yulivan, Ivan; Nawir, Jubaedah; Martiana, Anisa (LPPM Universitas Jambi, 2026)
Decades of defense industry scholarship have produced something quietly remarkable: a literature that speaks extensively about states, procurement systems, and geopolitical structures, yet has never once named the entrepreneurial actor at its center. This study asks, for the first time, whether that silence is incidental or structural. Drawing on two Scopus-derived corpora constructed through PRISMA 2020 protocol and analyzed via Bibliometrix and Biblioshiny in R, the study employs keyword co-occurrence network analysis, thematic mapping, Bradford's Law source distribution, and trend topic profiling. The global corpus comprises 1,797 documents (2000–2025); the Indonesian corpus, derived through systematic screening of 51 pre-PRISMA documents, yields 20 publications for gap analysis. Across 7,933 unique index keywords, entrepreneurship ranks 213th (n=7) and fails to achieve co-occurrence network inclusion; compound terms including defense entrepreneurship, startup, and venture capital return near-zero or zero occurrences. The Indonesian corpus reproduces this silence entirely: across 151 unique index keywords, entrepreneur, startup, SME, and venture capital are collectively absent. For Indonesia (a country whose defense modernization program achieved only 65% of its targets over fifteen years) this result is not merely an academic gap. It is a signal that feedback mechanism has been missing. This study positions defense entrepreneurship as a priority research frontier and calls for deliberate concept formation at the intersection of entrepreneurship theory and defense industrial policy.